2016
DOI: 10.5551/jat.34454
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Exercise-Based Cardiac Rehabilitation on High-Density Lipoprotein-Mediated Cholesterol Efflux Capacity in Patients with Acute Coronary Syndrome

Abstract: Aim: Recent studies reported that low high-density lipoprotein (HDL)-mediated cholesterol efflux capacity rather than low HDL cholesterol (HDL-C) is strongly associated with the increased risk for coronary artery disease. It remains unclear whether exercised-based cardiac rehabilitation (CR) can increase HDL cholesterol efflux capacity. Method: This study is a retrospective analysis of stored serum from patients with acute coronary syndrome (ACS) who participated in outpatient CR program following successful p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 47 publications
2
20
3
Order By: Relevance
“…8 Further, Koba and Ikewaki showed that rehabilitation after acute coronary syndrome significantly improved HDL CE capacity. 9 These results should be interpreted with caution, because these studies were cross-sectional; however, 2 later cohort studies independently demonstrated that CE capacity was a negative risk factor for ASCVD. 10, 11 In this issue of the Journal, Jung et al report that in diabetic patients with dyslipidemia rosuvastatin 20 mg treatment increased HDL function as assessed by CE capacity, improved vascular endothelial function (flowmediated dilatation (FMD) of the brachial artery), reduced carotid intima-media thickness (cIMT), and favorably changed biomarkers related to lipid metabolism and atherosclerosis.…”
Section: Editorial Advance Publication By-j-stagementioning
confidence: 93%
“…8 Further, Koba and Ikewaki showed that rehabilitation after acute coronary syndrome significantly improved HDL CE capacity. 9 These results should be interpreted with caution, because these studies were cross-sectional; however, 2 later cohort studies independently demonstrated that CE capacity was a negative risk factor for ASCVD. 10, 11 In this issue of the Journal, Jung et al report that in diabetic patients with dyslipidemia rosuvastatin 20 mg treatment increased HDL function as assessed by CE capacity, improved vascular endothelial function (flowmediated dilatation (FMD) of the brachial artery), reduced carotid intima-media thickness (cIMT), and favorably changed biomarkers related to lipid metabolism and atherosclerosis.…”
Section: Editorial Advance Publication By-j-stagementioning
confidence: 93%
“…The present study enrolled patients with ACS that followed successful percutaneous coronary interventions (PCI) between August 2005 and May 2015, and all of the studied patients were distinct from the patients in our previous study 12 ) . The diagnoses of ACS were based on electrocardiographic changes and coronary arteriograms.…”
Section: Methodsmentioning
confidence: 99%
“…Comprehensive cardiac rehabilitation (CR) has been shown to be beneficial in improving exercise capacity, quality of life, and/or prolonging survival in patients with CAD 11 ) . Recent our preliminary study was the first to show that a six-month CR program significantly increased CEC as well as HDL-C and apoA-I in 57 patients with acute coronary syndrome (ACS), whereas those changes were not seen in 11 patients who dropped out from the outpatient CR program; increases in CEC were significantly correlated to increases in HDL-C and apoA-I 12 ) . It is conceivable that CR may improve PON1 activity as well as CEC.…”
Section: Introductionmentioning
confidence: 96%
“…As shown in Framingham Heart Study 8) and Ludwigshafen Risk and Cardiovascular Health Study 9) , the plasma CETP activity/mass was negatively correlated with the incidence of CHD. Furthermore, the cholesterol efflux capacity from macrophage has a strong inverse association with CHD independent of serum HDL-C levels 10) and is improved by the physical exercise in patients with acute coronary syndrome 11) . Besides the cholesterol efflux or RCT, HDL has various capabilities such as anti-inflammatory, anti-oxidation, and anti-thrombotic functions 12) , the impaired functions of HDL may lead to the development of CV events.…”
Section: See Article Vol 23: 800-809mentioning
confidence: 99%